Biochemical changes and antioxidant capacity of naringin and naringenin against malathion toxicity in Saccharomyces cerevisiae - Gercek, Ezgi; Zengin, Hatayi; Erisir, Figen Erdem; Yilmaz, Okkes (Elsevier Science Inc, 2021)
Flavonoids are rich in seeds, citrus fruits, olive oil, tea and red wine. Citrus flavonoids constitute an important type of flavonoids. Naringin and naringenin belong to flavonoids with known antioxidant and were found to display antioxidant activities. Malathion is an organophosphorus pesticide that has been broadly used throughout the world to control weeds and pests. It has also been used in public health for mosquito control and fruit fly eradication programs. Malathion, naringin, and naringenin were added to be in 40, 80, and 160 mg doses in Saccharomyces cerevisiae cultures mainly used to determine the antioxidant capacity, it is known that they have shown similar results to man. At the end of the experiment, total protein, malondialdehyde (MDA), reduced glutathione (GSH), oxidized glutathione (GSSG), vitamin K, vitamin E, vitamin D, ergosterol, stigmasterol, beta-Sitosterol, and fatty acids were analyzed by HPLC (high performance liquid chromatography) and GC (gas chromatography) devices in the tested S. cerevisiae samples. The contents of the yeast cell of octanoic acid (C8:0), lauric acid (C12:0), myristic acid (C14:0), palmitic acid (C16:0), palmitoleic acid (C16:1n-7), heptadecanoic acid (C17:0), stearic acid (C18:0), oleic acid (C18:1n-9), and linoleic acid (C18:2n-6) were identified. There were statistically significant changes in total protein, MDA, GSH, GSSG, vitamin K, vitamin E, vitamin D, phytosterol and fatty acid levels. It was determined that naringin and naringenin showed statistically significant decreases against malathion toxicity on these parameters. From this study it is found that, the mitigating effect of naringin against DPPH stable free radical was higher than that of naringenin. Citrus flavonoid, naringin showed promising antioxidant activity which can be used as effective protecting agents against oxidative stress.
Keywords: Malathion; Naringin; Naringenin; GSH; GSSG; MDA; Fatty acid; Vitamins; Flavonoids; Saccharomyces cerevisiae